(untitled) (Bisanzio e l’Occidente, 2021)
The Epitome composed by John Kinnamos constitutes one of the few historical accounts contemporary to the reign of the Byzantine emperor Manuel I Komnenos (1143-1180). This period has often been approached as one of relative prosperity for the Byzantines, in contrast to the more troublesome decades at the end of the century, characterised by the rising tensions with the Latin polities from Western Christianity leading to the Fourth Crusade. Researchers have approached twelfth century Byzantine history precisely from the viewpoint of later disaster involving the relation between Byzantines and Latins. This article aims to bring evidence regarding Kinnamos’ approach to these relations, particularly those sections where the author seems to praise or at least tolerate Latin deviations from the Roman «normality».